Analysis of the effect of metal ions on the ability of Xylanase to hydrolyze wheat bran by molecular dynamics simulations - Hou, Mingrui; Liang, Chuanqi; Fei, Yanan; Yang, Dan; Zhang, Ningjing; Lu, Yujie; Wang, Lei; Xing, Zhiqiang; Zhao, Zongpei (Frontiers in Bioengineering and Biotechnology, 2023)
Wheat bran is the main by-product of wheat processing, containing about 30% pentosan and 0.4% to 0.7% ferulic acid. Wheat bran is the main raw material used to prepare feruloyl oligosaccharides by hydrolysis of Xylanase, we discovered that the ability of Xylanase to hydrolyze wheat bran could be affected in the presence of different metal ions. In the present study, we have probed the effects of different metal ions on the hydrolysis ability of Xylanase on wheat bran and tried to analyze the effect of Mn2+ and Xylanase at a molecular level by molecular dynamic (MD) simulation. Our results suggested that Mn2+ had improved the Xylanase hydrolyzing wheat bran to obtain feruloyl oligosaccharides. Particularly when the concentration of Mn2+ reached 4 mmol/L, the optimal product has been obtained 2.8 times higher to compare with no addition. Through the MD simulation analysis, our results reveal that Mn²⁺ can induce structural change in the active site, which enlarges the substrate binding pocket. The simulation results also revealed that the addition of Mn²⁺ resulted in a low RMSD value compared with the absence of Mn²⁺ and helped stabilize the complex.